Holocene hunter-gatherers and adhesive manufacture in the West Coast of South Africa - (:unkn) unknown (My University, 2016)
Elands Bay Cave provides the opportunity to characterize Holocene technologies and hunter-gatherers adaptations in the West Coast of South Africa. In this paper, we discuss the question of adhesives uses and manufactures by applying a biomolecular and technological analysis to three unpublished organic artefacts recovered from the 1970s excavation. The first piece is a large handle made of adhesive and with a tear-drop shape (the ‘handle’), the second piece is a kind of pencil grip wrapping a microlithic quartz segment (the ‘grip’), and the last piece takes the form of a macro-residue likely sealing the perforation of an ostrich eggshell flask (the ‘sealant’). The results of our study document the selection and transformation of Podocarpus resin, mixed with quartz sand to produce adhesive. One case study (the sealant) suggests that fat was added to the recipe in order to modify the adhesive’s properties. The paper provides a unique insight into Holocene organic technologies and fuels ideas on how hunter-gatherers adapted and took benefit from local natural resources. We suggest that Podocarpus, in South Africa, has been specifically chosen for adhesive manufacture since, at least, the MIS4.
Keywords: African Research